Multimodal therapy with surgery and adjuvant nivolumab for late-onset multiple liver metastases of choroidal malignant melanoma: a case report - Ryuta Muraki; Yoshifumi Morita; Shinya Ida; Ryo Kitajima; Satoru Furuhashi; Ryota Kiuchi; Makoto Takeda; Hirotoshi Kikuchi; Yoshihiro Hiramatsu; Takanori Sakaguchi; Akira Kasuya; Yoshihiro Hotta; et al. (Surgical Case Reports)
Abstract Background Choroidal malignant melanoma is the most common primary malignant tumor of the eye in adults. Prognosis after recurrence of this disease has been dismal because of the absence of an effective therapy. However, resection of recurrent foci and a subsequent treatment with immune-checkpoint inhibitor may improve the prognosis after recurrence of this disease. This study presents a case of late-onset liver metastases of choroidal malignant melanoma, successfully treated with hepatectomy and postoperative adjuvant nivolumab. Case presentation A 53-year-old woman had undergone left ocular enucleation because of choroidal malignant melanoma 13 years prior to admission. She visited a nearby clinic with complaints of epigastric pain. She was referred to our hospital because a giant liver tumor was observed on abdominal ultrasonography. Enhanced computed tomography revealed multiple liver tumors in the right lobe, 49 mm in diameter with ring enhancement in subsegment (S) 5/6, and 14 and 8 mm without any enhancement in S7 and S5, respectively. On magnetic resonance imaging, the main tumor showed high intensity on T1-weighted with fat suppression, suggesting melanin deposition. Based on the diagnosis of multiple liver metastases of choroidal malignant melanoma, right hepatectomy and regional lymphadenectomy were performed. She was discharged without postoperative complications. Histological examination revealed that all tumors were metastatic malignant melanoma. She was treated with nivolumab postoperatively, and no recurrences were observed during 22 months of follow-up. Conclusions Aggressive surgery plus adjuvant nivolumab appears to be a promising treatment for choroidal malignant melanoma with late-onset liver metastases.